2015
DOI: 10.17219/acem/33827
|View full text |Cite
|
Sign up to set email alerts
|

Brdt Bromodomains Inhibitors and Other Modern Means of Male Contraception

Abstract: Compared to efficient and secure female contraception, a vasectomy and condoms are the only options for men. The choice of male contraceptive methods is limited, so contraception mainly rests on the shoulders of women. Several concepts are considered: testosterone administration -inhibiting pituitary secretion of lutropin (LH) and follicle stimulating hormone (FSH), progestogen -affecting the secretion of gonadotropin and gonadoliberin (GnRH) antagonists. New potential targets for non-hormonal male contracepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(62 reference statements)
0
2
0
3
Order By: Relevance
“…The studies conducted on male reproductive cells of mammals (man and mouse) showed that bromodomain inhibitor JQ1 blocked BRDT, and the effects of its activity depended on the time of application and its dose. JQ1 affected the developmental stages of these cells already during meiosis and successive post-meiotic stages [43,50]. In the studied alga, it was not possible to examine how JQ1 treatment affected meiosis, because Chara has a different type of meiosis (to plants and mammals), which occurs only after fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted on male reproductive cells of mammals (man and mouse) showed that bromodomain inhibitor JQ1 blocked BRDT, and the effects of its activity depended on the time of application and its dose. JQ1 affected the developmental stages of these cells already during meiosis and successive post-meiotic stages [43,50]. In the studied alga, it was not possible to examine how JQ1 treatment affected meiosis, because Chara has a different type of meiosis (to plants and mammals), which occurs only after fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…a spermiumok mozgását gátolhatja, amely segítségével a hím ivarsejtek progresszív motilitása megszüntethető, így a fogamzásgátló hatás elérhető [47]. Alternatív lehetőség a Sertoli-sejtek és a korai fázisban lévő spermium-előalakok közötti sejt-sejt kapcsolat megszakítása, amely a spermiogenezis blokádját jelenti.…”
Section: Egyéb Nem Hormonális Lehetőségekkitekintésunclassified
“…Alternatív lehetőség a Sertoli-sejtek és a korai fázisban lévő spermium-előalakok közötti sejt-sejt kapcsolat megszakítása, amely a spermiogenezis blokádját jelenti. Az erre alkalmas vegyületek (adjudin, gamendazol, CDB-4022) humán alkalmazása egyelőre vesekárosító hatásuk miatt nem kivitelezhető, de a jövőben a mellékhatásprofil optimalizálása mellett fogamzásgátlásra alkalmasak lehetnek [47].…”
Section: Egyéb Nem Hormonális Lehetőségekkitekintésunclassified
See 1 more Smart Citation
“…These methods target a specific protein when inhibited by small molecules, or knocked out in mice will lead to infertility. Although these leads have enormous promise and preclinical studies are ongoing, clinical studies have not yet started (Tash et al, 2008;Chung et al, 2011;Matzuk et al, 2012;Paik et al, 2014;Zdrojewicz et al, 2015; O'Rand et al, 2016).…”
mentioning
confidence: 99%